2020
DOI: 10.3390/ijerph17176300
|View full text |Cite
|
Sign up to set email alerts
|

Night Shift Work, Chronotype, Sleep Duration, and Prostate Cancer Risk: CAPLIFE Study

Abstract: To analyze the association between prostate cancer (PCa) risk and night shift work, chronotype, and sleep duration in the context of a population-based case-control study of incident prostate cancer in Spain, a total of 465 PCa cases and 410 controls were analyzed. Selection criteria were: (i) age 40–80 years, and (ii) residence in the coverage area of the reference hospitals for ≥6 months before recruitment. Exposure variables were: (i) night shift work (permanent or rotating); (ii) chronotype: morning, neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 52 publications
4
31
0
Order By: Relevance
“…Similarly, for patients engaged in night-shift work, the synthesis of PER1, PER2 and CRY2 will not decrease as long as retinal neurons receive light signals continuously, and the expression of androgen and AR will not increase thereby. Thus, the PCA risk does not increase significantly, which is consistent with the results of previous epidemiological studies (19,20). Indeed, the chronic CDH disorder caused by staying up or night-shift work might increase PCA risk through other factors, such as metabolic syndrome and inflammatory bowel disease (72)(73)(74)(75)(76)(77).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, for patients engaged in night-shift work, the synthesis of PER1, PER2 and CRY2 will not decrease as long as retinal neurons receive light signals continuously, and the expression of androgen and AR will not increase thereby. Thus, the PCA risk does not increase significantly, which is consistent with the results of previous epidemiological studies (19,20). Indeed, the chronic CDH disorder caused by staying up or night-shift work might increase PCA risk through other factors, such as metabolic syndrome and inflammatory bowel disease (72)(73)(74)(75)(76)(77).…”
Section: Discussionsupporting
confidence: 88%
“…It has been previously observed that genetic variants of CIC genes might be related to PCA progression (14)(15)(16)(17)(18). However, so far, there has been little agreement on whether night shift work is associated with increased PCA risk (19)(20)(21). Thus, we proposed that CIC mainly promotes PCA development and progression through indirect mechanisms, such as androgen receptor (AR) (7), ep ith el ial -me se nch ym al tr a nsi tion an d the tu m or microenvironment (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that rotating shift workers, but not fixed shift workers, were associated with a higher risk of increased PSA compared with daytime workers. This result was in line with previous studies indicating that rotating shift workers were more prone to have prostate cancer [ 13 , 14 ]. Mancio et al explained that more severe disruption of the circadian rhythm due to insufficient time for the circadian clock to adapt and consequently lower melatonin levels during the sleep period for rotating shift workers than fixed shift workers result in a higher risk of prostate cancer [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, several studies have shown associations between shift work and prostate cancer, but these studies were few and lacked consistency [ 9 ]. To date, despite a limitation of inconsistency, several studies have demonstrated a positive association between shift work and prostate cancer, especially in rotating shift workers [ 12 , 13 , 14 ], and such a relationship cannot be ignored. In this sense, it is reasonable to evaluate a more temporal relationship between shift work and prostate cancer by a longitudinal study.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythm disruption can contribute to suppress melatonin, which is a neurohormone known for its role in hindering cancer initiation and progression (9)(10)(11). Recent studies have demonstrated that circadian disruption might play a role in the etiology of cancers, including colorectal cancer, gastric cancer, prostate cancer, and breast cancer (12,13). However, the mechanisms for the circadian rhythm in cancer are not well elucidated.…”
Section: Introductionmentioning
confidence: 99%